THE INFLUENCE OF THE ENVIRONMENT AND PARENTING STYLE ON CHILDREN IN RELIGIOUS TOLERANCE IN MANANTI VILLAGE, HUTARAJA TINGGI DISTRICT: PENGARUH LINGKUNGAN DAN POLA ASUH ORANG TUA TERHADAP ANAK DALAM BERTOLERANSI BERAGAMA DI DESA MANANTI KECAMATAN HUTARAJA TINGGI - Manna Harahap; Syarbaini Saleh (SOSIOEDUKASI, 2025)
This study aims to find out and analyze the influence of social environment and parental parenting on religious tolerance behavior in children in Manoni Village, Hutaraja Tinggi District. Religious tolerance is an important attitude in the life of a pluralistic society, and its formation is greatly influenced by internal factors in the family as well as external factors from the surrounding environment. This study uses a qualitative approach with a case study method. Data was obtained through in-depth interviews, field observations, and documentation of a number of informants, including parents, teachers, community leaders, and children. The results of the study show that an open, harmonious, and mutually respectful social environment plays a major role in shaping children's tolerant attitudes towards religious differences. On the other hand, parents who are democratic, communicative, and provide real examples in religious life also have a significant influence on the way children understand and behave towards diversity. Children who were raised with an inclusive parenting approach and were in a supportive environment showed higher levels of tolerance compared to children who were raised authoritarianly or grew up in an exclusive environment. This study concludes that the synergy between the role of family and the environment is very important in fostering children's tolerance from an early age, in order to form a peaceful and respectful society in the midst of religious differences.